ANALISIS PERSEPSI MASYARAKAT TENTANG TRADISI KAWIN TUKAR DI DESA BALBALU KABUPATEN BURU: KAJIAN DALAM KONTEKS PENDIDIKAN LUAR SEKOLAH - Nevi Waimese; Abednego; Lokollo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze community perceptions of the barter marriage tradition (muka ptukar) in Balbalu Village, Buru Regency, from an informal education perspective. The research addresses the tension between traditional customs and modern values regarding freedom to choose a spouse. Using a descriptive quantitative approach, data was collected from 49 community members and 10 traditional leaders through observation, closed questionnaires, and documentation. The analysis employed descriptive statistics with percentage calculations. Results revealed that 38.7% of respondents were very familiar with the tradition, 42.8% were highly motivated to follow it, 61.2% expressed high satisfaction, and 63.2% perceived significant benefits. The findings indicate that despite conflicts with national marriage laws emphasizing freedom of choice, the majority of the community maintains positive perceptions toward this traditional practice, viewing it as essential for cultural preservation and family harmony. The tradition serves as informal education for transmitting cultural values to younger generations, though it requires balanced integration with modern educational principles to ensure children's rights and development. This research contributes to understanding how traditional customs function as informal educational systems in indigenous communities.